2008
DOI: 10.1103/physrevb.77.024511
|View full text |Cite
|
Sign up to set email alerts
|

Resonances between fluxons and plasma waves in underdamped Josephson transmission lines of stripline geometry

Abstract: We present experiments and theoretical studies on the propagation of Josephson fluxons and electromagnetic waves in parallel arrays of Josephson junctions in the limit of small discreteness. Locking between the fluxon rotation frequency and the frequency of the radiated electromagnetic waves leads to a series of resonances, which we observe on the dc-current-voltage characteristics of the arrays. The arrays consist of small Josephson junctions embedded in an annular superconducting stripline. The experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 15 publications
(21 reference statements)
2
40
0
Order By: Relevance
“…Here we show evidence that, for this type of array in the strong coupling regime, stable single and multiple flux-quanta propagation exists over broad bias current ranges. Our experiments also confirm predictions of the theoretical modeling of the complex dynamics of 2π kinks in the Frenkel-Kontorova model [9,[12][13][14][15][16][17]. Figure 1(a) displays a photo of a portion of the real device showing the open-ended [13] parallel array of small junctions.…”
supporting
confidence: 80%
See 2 more Smart Citations
“…Here we show evidence that, for this type of array in the strong coupling regime, stable single and multiple flux-quanta propagation exists over broad bias current ranges. Our experiments also confirm predictions of the theoretical modeling of the complex dynamics of 2π kinks in the Frenkel-Kontorova model [9,[12][13][14][15][16][17]. Figure 1(a) displays a photo of a portion of the real device showing the open-ended [13] parallel array of small junctions.…”
supporting
confidence: 80%
“…2 we observed in most of the cases switching from the lowest part of the Josephson current as shown by the horizontal arrows in the IVs: these indicate that static flux quanta trapped in the JTL start moving at a threshold current and generate a voltage. Thus, the Lorentz force needs a threshold current to overcome the potential barrier pinning flux quanta in their locations [5,12,13,17]. From the current-voltage characteristics of the test junction we also estimated the McCumber parameter [2] The evaluation of the inductance l 0 of a single section of the array (given the speed of light in the transmission line and the specific capacitance of the junctions) enables us to evaluate the discreteness parameter a ¼ ð2πl 0 I c =Φ 0 Þ 1=2 [5,11,12], where Φ 0 ¼2.07×10 −15 Wb is the magnetic flux quantum.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…c o m / l o c a t e / p h y s c results. For arrays of equidistant junctions, a recent study by Pfeiffer et al [13] analyzed the fine features of the first resonant step in terms of Cerenkov radiation between a sine-Gordon discrete kink (fluxon) and a cavity mode. For one junction placed arbitrarily in the strip, our theoretical study [14] revealed that all the linear modes are excited with different amplitudes.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…One can quote the perturbation analysis [6] and modulation instability studies [7] of a e-mail: khomeriki@hotmail.com the process, theoretical [8,9] and experimental [10,11] investigations of the resonances between fluxons and linear plasma oscillations, fluxon dynamics studies in case of coupled JTL-s [12,13], fluxon induced directed transport under homogeneous ac driving with broken time symmetry [14] and many other interesting phenomena. At the same time, much less studies have been devoted to the dynamics of nonlinear excitations under the local (boundary) driving: In this connection one should mention the investigation of hysteretic regimes appearing due to the phase locking effect between the boundary driving and breather type localizations [15][16][17] (where the breathing frequency coincides with the driver frequency [18][19][20]) or, on the other hand, boundary driving can maintain stationary motion of the fluxon which creates a new frequency in the system being an odd fraction of the driving frequency [21][22][23].…”
Section: Introductionmentioning
confidence: 99%